POLA MAKAN PINTAR: MENCEGAH MALNUTRISI DAN MENDUKUNG KECERDASAN ANAK SEJAK DINI - Titien Ruswanti; Rachma Hasibuan (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
The problem of malnutrition in early childhood is a global challenge that has a serious impact on children's physical, cognitive and social development. This research uses a Systematic Literature Review (SLR) approach to analyze the relationship between a balanced diet, nutritional status and children's intelligence. The research results show that high-quality nutritional intake, such as protein, healthy fats, complex carbohydrates, and micronutrients (iron, iodine, and omega-3), plays an important role in supporting children's brain development and cognitive function. Interventions based on nutrition education, teacher training and community programs have been proven effective in preventing malnutrition and supporting optimal child growth and development. Integrated education for parents and teachers, strengthening micronutrient-rich nutrition programs, and regular monitoring of nutritional status are important steps to prevent malnutrition. Implementing technology-based approaches such as precision nutrition can also provide more personalized solutions in meeting children's nutritional needs. This research emphasizes the importance of multi-stakeholder collaboration in overcoming child malnutrition to support their intelligence potential in the future.